An Analysis of the Implementation of Physical Education Program of President Ramon Magsaysay State University Iba, Zambales, Philippines - Dizon, Donabel (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This research study aimed to evaluate the implementation of the Physical Education Program of President Ramon Magsaysay State University, Zambales, Philippines. Program evaluation of the Physical Education Program is towards providing quality learning opportunities, appropriate instruction, meaningful and challenging content for all learners. A total of forty eight PE teachers from the seven campuses of the said University participated in the study, which was conducted during the Second Semester, year 2024. The study employed descriptive quantitative research design and used survey questionnaire as data gathering instrument. It was found that the PE Teachers are young adults males; bachelor’s degree holders with master’s units; holds permanent position and have been teaching for more than a decade. Under the curricular aims aspect of program implementation, always implemented was the assurance that learners can demonstrate the understanding of basic games, rhythmic and gymnastics skills; individual/dual sports fundamental skills under curriculum contents were always implemented; the teachers always manifested confidence on subject matter/content; always utilized the demonstration teaching method and conventional and alternative assessment tools and techniques; promoted and advocated lifelong physical activity and movement; and used indoor and outdoor facilities and equipment for PE classes. Big class size, unfavorable attitudes of students towards PE, overloading class schedule were the issues and problems encountered in the implementation of PE Program in University. The University may employ strategies to further build the relevance and importance of sports, physical activities and PE in various aspects of life and policy changes focused on increasing class time and training teachers on updated curricula.